Seeds of change: Enhancing availability and adoption of new sorghum, groundnut, and bean varieties in Tanzania - Ochieng, Justus; Mwakatwila, Atupokile; Radegunda, Kessy; Steinke, Jonathan; Kalemera, Sylvia; Theophil, Areth; Chima, Richards; Mwenda, Emmanuel; Daudi, Happy; Kadege, Edith; Ojiewo, Christopher; Rubyogo, Jean Claude (2024)
Traders, offtakers or aggregators and institutional buyers are crucial in driving and creating demand pull in the entire commodity value chain, thus ACCELERATE project focus on engaging them with new varietal opportunities and connecting them to reliable seed sources to accelerate varietal adoption and turn over in Tanzania. The objective is to evaluate how effective this demand-pull stimulates bean, groundnut, and sorghum seed sector growth in Tanzania. This brief number 2 provides key activities accomplished so far from January to April 2024. The key messages are: